Dialog Umat Islam dan Kristen Di Kota Cilegon Banten - Hardian, Hardian (Tasamuh: Jurnal Studi Islam, 2015)
Indoctrination is a doctrine of pluralism in the world. The Doctrine is an indoctrination living in the world. It can be seen from electronic media and the others, both via seminar, political event, media conference and in academic studies in campus. The term of pluralism brings to pro and contra between each other. There is who understands pluralism in as religion. The pluralism must be understood as sunnatullah and the reality of the world. In this case, the dialogue is something important each other. So, to build good connection between human beings must be done and the understanding the tradition of religion in the world has to be raised. The religion is doctrine, so there is inter-subjective. The article explores that.